The electro-oxidation of carbon monoxide and ethanol on supported Pt nanoparticles: The influence of the support and catalyst microstructure - Ciapina, Eduardo G. [UNESP]; Santos, Sydney F.; Gonzalez, Ernesto R. (Springer Nature, 2013)
The sluggish kinetics of ethanol oxidation on Pt-based electrodes is one of the major drawbacks to its use as a liquid fuel in direct ethanol fuel cells, and considerable efforts have been made to improve the reaction kinetics. Herein, we report an investigation on the effect of the Pt microstructure (well-dispersed versus agglomerated nanoparticles) and the catalyst support (carbon Vulcan, SnO2, and RuO2) on the rate of the electrochemical oxidation of ethanol and its major adsorbed intermediate, namely, carbon monoxide. By using several structural characterization techniques such as X-ray diffraction, X-ray absorption spectroscopy, and transmission electron microscopy, along with potentiodynamic and potentiostatic electrochemical experiments, we show that by altering both the Pt microstructure and the support, the rate of the electrochemical oxidation of ethanol can be improved up to a factor of 12 times compared to well-dispersed carbon-supported Pt nanoparticles. As a result of a combined effect, the interaction of Pt agglomerates with SnO2 yielded the highest current densities among all materials studied. The differences in the activity are discussed in terms of structural and electronic properties as well as by mass transport effects, providing valuable insights to the development of more active materials. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Carbon monoxide; Direct ethanol fuel cells; Electrocatalysis; Ethanol; Metal-support interactions; Nanoparticles; Adsorbed intermediates; Agglomerated nanoparticles; Carbon-supported Pt nanoparticles; Electrochemical experiments; Sluggish kinetics; Structural and electronic properties; Structural characterization; Agglomeration; Carbon; Direct ethanol fuel cells (DEFC); Electrochemical oxidation; Electronic properties; Metal nanoparticles; Microstructure; Reaction kinetics; Transmission electron microscopy; X ray absorption spectroscopy; X ray diffraction; Platinum